In situ deposition of silver nanoparticles on polydopamine-coated manganese ferrite nanoparticles: Synthesis, characterization, and application to the degradation of organic dye pollutants as an efficient magnetically recyclable nanocatalyst - Gurbuz, Mustafa Ulvi; Elmaci, Gokhan; Erturk, Ali Serol (WILEY, 2021)
The present paper reports a facile in situ synthesis strategy for the production of MnFe2O4@PDA-Ag magnetically recyclable core-shell nanospheres by the deposition of silver nanoparticles (AgNPs) to the surface of MnFe2O4@PDA nanocomposites through the reduction of silver ions by the outer polydopamine (PDA) layer. The deposition of AgNPs over MnFe2O4@PDA was validated by scanning electron microscopy-energy-dispersive X-ray spectroscopy (SEM-EDX), transmission electron microscopy (TEM), thermogravimetric analysis (TGA), X-ray diffraction (XRD), and vibrating sample magnetometer (VSM) analysis. The catalytic reduction performance of the obtained MnFe2O4@PDA-Ag nanospheres were tested over model organic dye pollutants (i.e., methylene blue [MB] and 4-nitrophenol [4-NP]) by sodium borohydride. Notably, the as-prepared MnFe2O4@PDA-Ag nanocatalyst exhibited significantly enhanced catalytic activity for the reduction of MB (296.52 s(-1) g(-1)) and 4-NP (92.02 s(-1) g(-1)) compared with the other types of similar Ag- and PDA-based catalytic systems in the recent literature. Moreover, the MnFe2O4@PDA-Ag nanocatalyst showed excellent recyclability, ease of magnetic separation, and rapid and higher recovery ability with insignificant loss in their catalytic efficiencies even after several cyclic uses. The PDA coating on the surface of MnFe2O4 NPs allocates the surface functionalization for the building of novel catalyst systems. This work presents a simple and practicable for the synthesis of MnFe2O4@PDA-Ag nanospheres that could have a great potential for the treatment of organic pollutants in wastewater and variety of applications in catalysis.
Keywords: catalytic reduction; dye removal; magnetic core– shell nanospheres; polydopamine (PDA); water treatment; CORE-SHELL MICROSPHERES; CATALYTIC-REDUCTION; GREEN SYNTHESIS; SURFACE MODIFICATION; METHYLENE-BLUE; DOPED CARBON; NANOCOMPOSITES; SILICA; EXTRACT; PERFORMANCES; Chemistry